2016
DOI: 10.1002/jssc.201501302
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of structurally related aliphatic amino alcohols in l‐valinol by hydrophilic interaction liquid chromatography separation combined with postcolumn derivatization and fluorescence detection

Abstract: The amino alcohols in l-valinol were effectively separated and quantified using hydrophilic interaction chromatography with fluorescence detection. The influence of the mobile phase (salt type, buffer concentration, and pH) on retention was studied. A column TSKgel amide and mobile phase consisting of 10 mM acetate buffer pH 4.0 and acetonitrile (20:80, v/v) provided well-separated symmetric peaks of analytes. Fluorescence detection was performed using postcolumn derivatization with o-phtaldialdehyde/2-mercapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The influence of flow rate of derivatization reagent , the derivatization reagent concentration and pH , temperature of derivatization reaction , and finally the volume of capillary coil reactor on the fluorescence detector response have been investigated for the conditions of postcolumn derivatization. The influence of the molecular structure on detector response during derivatization reaction of amines with OPA has already been shortly discussed . The response factors (RF) of tested compounds related to methylamine or cyclobutylamine were determined using the following equation: RF=A REF c REF c DET A DET where A REF stands for response of reference compound, A DET is response of a tested compound, c REF is concentration of reference compound, and c DET is concentration of a tested compound.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of flow rate of derivatization reagent , the derivatization reagent concentration and pH , temperature of derivatization reaction , and finally the volume of capillary coil reactor on the fluorescence detector response have been investigated for the conditions of postcolumn derivatization. The influence of the molecular structure on detector response during derivatization reaction of amines with OPA has already been shortly discussed . The response factors (RF) of tested compounds related to methylamine or cyclobutylamine were determined using the following equation: RF=A REF c REF c DET A DET where A REF stands for response of reference compound, A DET is response of a tested compound, c REF is concentration of reference compound, and c DET is concentration of a tested compound.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, it was shown that the application of postcolumn derivatization is more suitable due to simplicity and instability of the OPA fluorescent derivatives . The influence of flow rate of derivatization reagent , the derivatization reagent concentration , buffer pH , temperature of derivatization reaction , and finally the volume of capillary coil reactor on detector response have been investigated for the conditions of postcolumn derivatization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 The detailed procedure of IN is described in the literature. The final chromatographic conditions were optimized to obtain retention factor k ≥ 2, efficiency N ≥ 6000 for first eluting enantiomer and to achieve baseline separation (resolution R S ≥ 2.0).…”
Section: Evaluation and Validation Of Methodsmentioning
confidence: 99%
“…24 The sample solutions of L-Valinol at concentration of 10 μg/mL with different additions of D-Valinol (the concentration range from LOQ to 200% of the target specification limit with respect to L-Valinol sample solution, the 100% specification limit corresponded to 0.015 μg/mL) were prepared. 24 The sample solutions of L-Valinol at concentration of 10 μg/mL with different additions of D-Valinol (the concentration range from LOQ to 200% of the target specification limit with respect to L-Valinol sample solution, the 100% specification limit corresponded to 0.015 μg/mL) were prepared.…”
Section: Limit Of Detection and Quantification Accuracy And Lineamentioning
confidence: 99%